A laboratory study to disentangle hydrological, mechanical and structural mechanisms of soil stabilization by plant mucilage between eroding and depositional zones of a slope. (23rd March 2020) - Zhong, Xiao‐lan; Li, Jiang‐tao; Naveed, Muhammad; Raffan, Annette; Hallett, Paul D.
Abstract: Biological exudates, such as plant mucilage, can greatly stabilize soils, but as the mechanical and hydrological drivers depend much on soil particle size composition, eroding and depositional areas of a slope may respond differently. Soils from an eroded midslope and a depositional footslope in an arable farm were amended with chia ( Salvia hispanica ) seed mucilage at concentrations of 0 g C kg −1, 0.46 g C kg −1 and 2.3 g C kg −1 mucilage, formed into cores, and then imparted with wetting and drying (WD) cycles. Mucilage increased the stability of these inherently stable soils from 80% to >98% water‐stable macroaggregates at 0 WD cycles regardless of slope position. Aggregate stability was maintained after 5 WD cycles by mucilage, whereas the stability of unamended soil dropped by 66.7% in the footslope and 30.1% in the midslope compared with 0 WD. The underlying physical stability properties were measured by tensile strength and penetration resistance for mechanical properties, water sorptivity and repellency for hydrological properties, and micro‐, meso‐, macro‐ and total porosity for structural properties. Almost every soil physical property measured changed less with WD cycles if mucilage was present. Compared to unamended soil, 2.3 g C kg −1 mucilage amendment decreased water sorptivity from 0.289 mm s −1/2 to 0.122 mm s −1/2 in the midslope and 0.230 mm s −1/2 to 0.182 mm s −1/2 in the footslope after 5 WD cycles. Aggregate stability, total porosity and water sorptivity were correlated. In the midslope, hydrology and penetration resistance were affected the most, which was likely to be driven by mucilage deposition in the macropores of this more coarsely textured soil. In the footslope, the greater impact of mucilage on tensile strength was likely to be driven by buffering of macroporosity formation by WD cycles in this finer‐textured soil. Highlights: We explored how slope position interacts with plant mucilage to drive soil physical stability. Changes in soil physical stability by plant mucilage have rarely been considered with slope position. Interactions between mucilage and soil particles caused greater physical stability in the midslope than footslope. Mucilage stabilized soil by easing changes in pore structure, DOC redistribution and water repellency, with particle bonding less important.